Winner takes all [large type] - Kitt, Sandra (The millionaires club, 2021)
"Jean Travis has the job of announcing the latest lottery winner on TV and is stunned to find that Patrick Bennett, her teenage crush, is the top mega winner. They haven't seen each other in years, and Patrick is thrilled to renew their acquaintance. Jean, not so much. After all, a lot has changed since they used to study together and Jean worked so hard to hide her feelings. Now that he's won so much money, Patrick faces a whole new world of demands from family, friends, coworkers, strangers. The only person he knows for sure he can trust is Jean"--Provided by publisher.